2022
DOI: 10.1097/jom.0000000000002525
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Assessment and Selection of Workforce Health Intervention Priorities for Correctional Supervisors

Abstract: Objective: A team of academics and unionized correctional supervisors collaborated to assess workforce health and determine intervention priorities using participatory methods and tools. Methods: Correctional supervisors took a web-based survey. Univariate and bivariate tests examined attitudes/ behaviors, exposures, and outcomes most strongly associated with health; risk based on rank within chain-of-command; and health behaviors amenable to change. We used a voting process tool to prioritize intervention top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The shared overtime policy also had the potential obstacle of requiring union contract negotiations. The underlying contradiction of overtime work also came into play, as our previous research found that not all supervisors would support initiatives to limit overtime that reduced income, even if it meant better sleep health 29,30 . The DT decided to tackle sleep habits due to the fact that it was a more agreeable topic to approach.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The shared overtime policy also had the potential obstacle of requiring union contract negotiations. The underlying contradiction of overtime work also came into play, as our previous research found that not all supervisors would support initiatives to limit overtime that reduced income, even if it meant better sleep health 29,30 . The DT decided to tackle sleep habits due to the fact that it was a more agreeable topic to approach.…”
Section: Resultsmentioning
confidence: 99%
“…As such, it was forwarded to union management to become a possible topic for future contract negotiation. Changes in work schedules also required considerable discussion within the union bargaining unit, because many supervisors value their overtime income and would resist any organizational changes that would reduce those opportunities 29,30 . The DT acknowledged that such an innovative intervention would require some education of the workforce on the consequences of long work hours for sleep and health, and needed more support from the ranks to move forward.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations